Uma análise comparativa entre capitais econômico e regulamentar com enfoque em risco de mercado - Veiga, Letícia Gentile da (2008)
In this work, we analyze the methodology developed by the Central Bank of Brazil, following rules set by Basel II, for estimating the Capital that must be held by Brazilian Banks in order to face its financial risks. The main objective is to compare this regulatory capital to the economic capital, the latter being measured by the methodology of Value at Risk (VaR). We asses and compare these two types of capital based on practical examples of portfolios commonly held by Brazilian banks trading different markets and strategies. Based on the results of this assessment, we analyze the difference and similarities of the two methodologies. We conclude emphasizing the importance of revising some aspects of Basel II rules in order to promote greater convergence between economic and regulatory capital.